Drilled Shaft Foundations for the Float-in Dam on the Monongahela River at Braddock, PA (6c19e969-5f09-43f8-9e6e-1837d4537e5e) - Robert B. Bittner (Deep Foundations Institute, 2007)
The new gated dam on the Monongahela River at Braddock, Pennsylvania, was built for the US Army Corps of Engineers using an innovative "In-the-Wef' technology. A key feature of this technology involves construction of the foundations through the water and later mating the completed structure or a shell of the structure to the pre-installed foundation. This paper presents a description of the structure, its foundation, construction sequence and design details required to successfully Implement this technology.